Engaging with the Qur'an Religious Practice and Daily Life of Selected Muslim Women in Finland and Egypt - Al-Sharmani, Mulki 1965- (2024)
In this article, I examine what selected Muslim women in Finland and Egypt do with the Qur'an in their daily lives. I shed light on their modes of engagement with the Qur'an (spiritual, emotional, intellectual, communal). I analyse how their relationship with the Qur'an is shaped and changes over the course of their life. I pay attention to the interplay between the women's daily lives and the ways in which they experience, learn from, grapple with, and interpret the text. My overall aim is twofold: to contribute to research-based understanding of the Qur'an as daily religious practice that in many ways involves learning both about God and about the complex circumstances of personal life, and to unpack the layered and shifting meanings of this practice in the context of the women's lives. My analysis is informed by life-story interviews with six women in Helsinki and Cairo (three in each country).
Keywords: Qur'an; Knowledge; Life experiences; Religious Practice; Women